2016
DOI: 10.1016/j.jpainsymman.2015.12.326
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Changes in Family Caregivers' Preferences for Life-Sustaining Treatments for Terminally Ill Cancer Patients at End of Life in the Context of a Family-Oriented Society

Abstract: Family caregivers' LST preferences for terminally ill cancer patients are a heterogeneous construct and shifted from uniformly rejecting all LSTs toward greater uncertainty. Surrogate EOL-care decision making may be facilitated by earlier and thorough assessments of caregivers' LST preferences and tailoring interventions to the unique needs of caregivers in each class identified in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…LSTpreference patterns have been reported separately for terminally ill cancer patients 32 and their family caregivers. 33…”
Section: Methodsmentioning
confidence: 99%
“…LSTpreference patterns have been reported separately for terminally ill cancer patients 32 and their family caregivers. 33…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, while relatives' views may reflect patients' real wishes, other authors have shown a more aggressive attitude of relatives regarding CPR and other life-sustaining treatments, failing to represent patients' views(Ackroyd et al, 2007;Hwang, Keam, Kim, & Yun, 2014;Tang, Liu, Lai, Liu, & Chen, 2005;Tang et al, 2016;Yun et al, 2011).In addition, most of our patients wished one relative to be present during CPR. Most patients (36%) tended to prefer a joint decision regarding their CPR status made by themselves, their family and their physician.…”
mentioning
confidence: 58%
“…35 Respecting patients' autonomy in Asian countries is further impeded by physicians' infrequently disclosing prognosis to cancer patients 35,36 and EOL care seldom being discussed between patients and their families. 37 Discussing issues about death and dying is taboo in Asia, 38 resulting in families inaccurately understanding patients' preferences 38,39 and projecting their own preferences to shape patients' EOL care (by overtreating or undertreating, as discussed in the following sections). 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 Time after enrollment, weeks LST-preference state probability, % Our findings of discordance between preferred and received LST states concur with reports that such discrepancies often tend toward patients receiving less aggressive care than they prefer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, even when patients clearly and uniformly rejected LSTs and families recognized that LSTs could cause unbearable suffering for patients in the life-sustaining-preferring and uncertain states, Taiwanese families might elect to forgo LSTs to avoid needlessly protracting the dying process but still insist on providing intravenous nutrition till the patient's death. 39…”
Section: Discussionmentioning
confidence: 99%